RNA-Cholesterol Nanoparticles Function as Potent Immune Activators via TLR7 and TLR8 - Obermann, Hannah-Lena; Lederbogen, Ines I.; Steele, Jenny; Dorna, Jens; Sander, Leif Erik; Engelhardt, Konrad; Bakowsky, Udo; Kaufmann, Andreas; Bauer, Stefan (Frontiers in Immunology, 2022)
The innate immune system senses viral and bacterial ribonucleic acid (RNA) via pattern recognition receptors (PRR) leading to subsequent activation of the immune system. One group of RNA sensors is formed by endosomal/lysosomal Toll-like receptors (TLR) such as TLR7 and TLR8. During viral or bacterial infection, immunostimulatory RNA is part of the pathogen reaching the endosomal/lysosomal compartment after cellular uptake. Synthetic single-stranded or double-stranded oligoribonucleotides (ORN) can mimic RNA from pathogens and are widely used as activating ligands for TLR7 and TLR8. However, one limitation in the use of synthetic ORN driven immune stimulation is the need for transfection reagents for RNA delivery into cells. Here we demonstrate that the conjugation of cholesterol to a double-stranded version of immunostimulatory RNA40 strongly enhanced RNA uptake into monocytes and plasmacytoid dendritic cells when compared to naked RNA. Cholesterol-conjugated RNA (RNA-chol) formed nanoparticles that were superior to RNA-liposomes complexes in regard to induction of type I interferon from human and murine plasmacytoid dendritic cells as well as proinflammatory cytokine production (e.g. TNF-α, IL12p70 or IL-6) in human monocytes. Furthermore, the RNA40-chol induced cytokines in human monocyte cultures supported TH1 and TFH cell differentiation underscoring a strong adjuvant function of RNA-chol nanoparticles for adaptive immune responses. In summary, cholesterol-conjugated immunostimulatory RNA forms nanoparticles and functions as a potent immune adjuvant in human and murine immune cells. It further simplifies the use of immunostimulatory RNA by avoiding the need for liposomal transfection reagents.